Lidocaine Shows Significant Antimicrobial Effects Against Staphylococcus Species: An In-Vitro Study Comparing Different Combinations of Lidocaine and Clinically Used Injectables, like Steroids and Hyaluronan, in the Context of Arthritis Management - Stephan Heller; Ricarda Johanna Seemann; Rainer Burgkart; Andreas Obermeier; Hermann Locher (Biomedicines)
Introduction: Intra-articular injections, commonly used in osteoarthritis treatment, are debated due to their potential link to septic arthritis, though its incidence remains low. Lidocaine, used as a “carrier” for therapeutic substances like hyaluronan or triamcinolone, has pain-relieving and antimicrobial properties. This study investigates the concentration-dependent antimicrobial effects of lidocaine in combination with hyaluronan and triamcinolone in both standard and synovial fluid cultures. Methods: The antimicrobial efficacy of lidocaine against Staphylococcus aureus was investigated, with variations in bacterial and lidocaine concentrations. Bacterial growth was monitored using a UV/VIS spectrometer at 600 nm. Lidocaine solutions of 1% and 2% were tested, both alone and in combination with hyaluronic acid or Triam40, in tryptic soy broth (TSB), to reflect knee joint applications. The groups included pure lidocaine (L), Triam (T), hyaluronan (H), and combinations (LT, LH, TH, LTH) with 1% or 2% lidocaine. A bacterial inoculum of 300 CFU/mL was used, and samples were incubated for 12 and 24 h. Additional tests were conducted on Staphylococcus epidermidis and methicillin-resistant Staphylococcus aureus (MRSA), as well as on S. aureus in human synovial fluid. Results: Lidocaine showed a concentration-dependent antimicrobial effect, with greater inhibition at higher concentrations and lower bacterial densities. All lidocaine-containing combinations significantly reduced the bacterial levels of S. aureus in TSB. Similar results were seen for S. epidermidis and MRSA, with notable inhibition in synovial fluid after 12 h, especially with 2% lidocaine. Conclusions: Lidocaine exhibits dose-dependent antimicrobial effects against key pathogens responsible for septic arthritis. Its combination with Triam40 and hyaluronan may reduce the risk of septic arthritis, supporting its clinical relevance.